UNKNOWN SPACE (FRONTIER) AS AN ENVIRONMENT FOR OVERCOMING CULTURAL BOUNDARIES - AVETISYAN, GHAZAR (Bulletin of Yerevan University E: Philosophy, Psychology, 2020)
A person's going beyond the boundaries of his own cultural space gave rise to a particular problem of meeting with an Alien in frontier heterotopy, where the formation of his image took place in the special conditions of cross-cultural dialogue. It was the frontier who formed a special picture of the world, in which the Alien was given a central place. Consideration of the frontier through the prism of a Foucalt heterotopic space, i.e. space, including many others, allows you to analyze taking into account the many actors of cultural dialogue, because frontier - a multicultural environment that includes many sociocultural components. Moreover, as a heterotopic space, frontier heterotopy includes all other heterotopies: crisis, extreme, open, closed, etc. Penetrating into the frontier territory, the subject becomes part of a new heterotopy and, in contact with the Alien here, seeks to displace him from this space, to replace him with himself. But this new space is perceived inseparably from the Alien, which turns out to be its peculiar attribute. It is this desire to fill a space with itself that acts as the main motive for transgression. As a result, new hybrid cultural spaces are being formed.
Keywords: frontier, heterotopy, culture, alien, boundary, breaking borders, transgression